TEACHERS AND PARENTS' PERSPECTIVES ON GIRL LEADERSHIP BEHAVIOR IN EARLY CHILDHOOD AT PG-TK NUANSA CENDIKIA - Aisyah Dwi Pertiwi, - (2021)
This study discusses the perspectives of teachers and parents regarding female/girls behavior in early childhood at PG-TK Nuansa Cendikia. Nowadays, gender is no longer an obstacle for individuals to develop their potential. Girls can be leaders in the future. However, society values still stifle and impede women in developing their potential, one of which is leadership behavior. Though leadership behavior is useful for them to be able to solve problems in life and take a bath. The purpose of this study was to determine the perspectives of teachers and parents, efforts, and obstacles as well as solutions. The approach used in this research is qualitative using descriptive method. The data collection techniques of this research used interviews and questionnaires. The results of the study shows that teachers and parents have the perspective that girls can become leaders and can be instilled from an early age through simple habits at home and at school. The obstacle that found is the stigma of society. The solution taken by teachers and parents is to communicate the stigma. The conclusion of this study is leadership behavior can also be owned by girls. The parents and teachers comprehension have a main role to support girls to be the leader in the future or even to lead themselves. This research is expected to provide responses to various parties who are stakeholders in developing leadership behavior in childhood girls.